ASSESSMENT OF THE ACOUSTICAL PERFORMANCE IN MALACCA MOSQUE,MALAYSIA: A CASE STUDY ON THE SAYYIDINA ABU BAKAR MOSQUE - Putra, Azma; Kassim, Dayang H.; YAAKOB, MOHD YUHAZRI; Abdullah, Y; Muhammad, Nor S.; Jenal, Rustamreen; Nor, Mohd Jailani M. (International of Acoustics and Vibration, 2013)
As a building for worship and one of the important symbols in Islam, a mosque is usually designed with its architectural grandeur. Among of the characteristics is its spacious interior to create a perception so that people will feel ’small’ when entering the house of God. Most mosques therefore have high ceiling and are usually constructed with dome shape. In Malacca, Malaysia however, the architectural of the mosque resembles the traditional Malay house where the ceiling follows a pyramidal shape. This paper discusses the acoustical condition of the mosque in Malacca. The Sayyidina Abu Bakar Mosque is presented here for a case study. Measurement of its reverberation time was conducted and the results are validated with simulation data from CATT room acoustics software. Other important acoustical parameters are evaluated such as the early decay time, clarity, definition, lateral fraction and speech transmission index.